Development of Spiritual Intelligence through the Learning of Aqidah Akhlak (Case Study of Madrasah Aliyah YTP Kertosono) - Isnaini muqit Ariyanto (STAI Miftahul Ula Nganjuk, 2024)
This article aims to elucidate the process of developing spiritual intelligence through learning in an Islamic high school (madrasah aliyah). Therefore, understanding of ethics and spirituality must be established as its foundation. In this madrasah, spiritual intelligence is cultivated through various methods, one of which is through the subject of aqidah akhlak (ethics and morality). This research adopts a qualitative field research approach, which involves procedures that generate descriptive data in the form of written or spoken words and observed behaviors. Data collection techniques include participant observation, in-depth interviews, and documentation. Data analysis employs reflective thinking (data reduction, data presentation, conclusion drawing). Data validity is checked through researcher involvement extension, observation diligence, triangulation, and auditing. The study reveals that planning begins with setting learning objectives, selecting methods, choosing media, and evaluation, all of which are accommodated in the lesson plans (RPP) derived from the syllabus, curriculum framework (prota), and annual program (promes). This investigation also finds that the implementation of this planning involves an emotional approach, where educators attempt to activate the affective domain of learners. Building positive behaviors among learners is done repeatedly using dogmatic, deductive, and inductive methods. The study also presents several outcomes after the implementation of the planning, such as a more conducive learning environment, improvement in the moral and spiritual aspects of learners, prevention of negative behaviors, control of learners' emotions, and the cultivation of strong aqidah and virtuous behavior among learners.